PENGARUH PROFITABILITAS DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - hotman tohir pohan; Ice Nasyrah Noor; Yudha Fatrya Bhakti (Jurnal Akuntansi Trisakti, 2018)
This research aim to analise the influence of profitability and corporate social responsibility disclosure using size of firm as moderation variable. In this research the sample used are non-profitable ventures as listed in Bursa Efek Indonesia (BEI) in 2014 until 2016. Source of information used in this research are financial statements, firms annual report, and sustainability reports. Corporate Social Responsibility disclosure is measured by sustainability reports wich is given score by general standard and specific standard in annual reports adjusted with directive sustainability Global Reporting Initiative gen 4 (GRI-G4) report. Build upon analisis from this research, writer can conclude that profitability weighs positive and has significant effect towards company values. Corporate Social Responsibility disclosure affected company values and weighs unsignificant towards company values.  Corporate Social Responsibility disclosure that uses company size as moderation variable  has unsignificant effect towards company values.